Reproducibility and accuracy of late gadolinium enhancement cardiac magnetic resonance measurements for the detection of left atrial fibrosis in patients undergoing atrial fibrillation ablation procedures. Issue 5 (10th January 2019) - Mărgulescu, Andrei D; Nuñez-Garcia, Marta; Alarcón, Francisco; Benito, Eva M; Enomoto, Norihiro; Cozzari, Jennifer; Chipa, Fredy; Fernandez, Hael; Borras, Roger; Guasch, Eduard; Butakoff, Constantine; Tolosana, Jose M; et al.
Abstract: Aims: Late gadolinium enhancement cardiac magnetic resonance (LGE-CMR) may define left atrial (LA) anatomy and structural remodelling, and facilitate atrial fibrillation (AF) ablation. We aimed to assess the intra- and inter-observer reproducibility and agreement of LGE-CMR parameters with direct application to AF ablation techniques. Methods and results: One experienced and one non-experienced observer performed complete LGE-CMR data analysis twice, on different days, in 40 randomly selected LGE-CMR examinations [20 performed before ablation (pre-ablation) and 20 performed 3 months after ablation (post-ablation)]. Four additional observers (two experienced and two non-experienced) performed complete LGE-CMR data analysis in a subgroup of 30 patients (15 pre-ablation and 15 post-ablation). All LGE-CMR were performed in sinus rhythm. Intra- and inter-observer reproducibility of LA volume, LA area, and sphericity index (SI) was high: coefficient of variation <10% and intraclass correlation coefficient >0.71. Geometric congruency of repeated reconstruction of LA shape was high: maximal error <5 mm for intra-observer and <8 mm for inter-observer. The precision of scar location increased with extent of scar, and was high (Dice coefficient >0.75) when the scar area was >5 cm 2 for a single observer and >15 cm 2 for multiple observers. Non-experienced observers performed equally well to experienced observers. Conclusion: Late gadolinium enhancement cardiac magnetic resonance measurements of LA area, volume, and SI were reproducible, and geometric congruency of LA shape was high. Location of scar was precise for scar areas >5 cm 2 for single observers and >15 cm 2 for multiple observers, regardless of the observers' experience. These results may serve as a reference for future studies on the role for substrate-based AF ablation procedures.